2014
DOI: 10.1242/jcs.135269
|View full text |Cite
|
Sign up to set email alerts
|

Deficits in receptor-mediated endocytosis and recycling in cells from mice bearing a disruption of the Gpr107 locus

Abstract: GPR107 is a type III integral membrane protein that was initially predicted to be a member of the family of G-protein-coupled receptors. This report shows that deletion of Gpr107 leads to an embryonic lethal phenotype that is characterized by a reduction in cubilin transcript abundance and a decrease in the representation of multiple genes implicated in the cubilin-megalin endocytic receptor complex (megalin is also known as LRP2). Gpr107-null fibroblast cells exhibit reduced transferrin internalization, decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 31 publications
2
14
0
Order By: Relevance
“…Overexpression of TMEM87B, a close homologue of TMEM87A and a member of the same family, also restored the defect in V54KO cells ( Figure 6A ; geometric means of cell surface levels of VFG-GPI and FVG-TM were 1.85 ± 0.22 and 3.42 ± 0.99 times, respectively, those in V54KO+Vec; n = 3), suggesting its functional redundancy with TMEM87A. Recently a role for GPR107—another LU7TM family member—was shown in retrograde transport of toxins such as exotoxin A of Pseudomonas aeruginosa and ricin ( Carette et al ., 2011a ; Elling et al ., 2011 ; Tafesse et al ., 2014 ; Zhou et al ., 2014 ). Unlike TMEM87A and TMEM87B, overexpression of GPR107 or GPR108, a member of LU7TM family closely related to GPR107, did not restore the delayed transport of either VFG-GPI or FVG-TM in V54KO cells ( Figure 6B ; geometric means of cell surface levels of VFG-GPI and FVG-TM in V54KO+GPR107 were 1.21 ± 0.38 and 0.98 ± 0.11 times, respectively, those in V54KO+Vec [ n = 2], and those in V54KO+GPR108 were 1.23 ± 0.14 and 1.15 ± 0.027 times, respectively, those in V54KO+Vec [ n = 2]).…”
Section: Resultsmentioning
confidence: 99%
“…Overexpression of TMEM87B, a close homologue of TMEM87A and a member of the same family, also restored the defect in V54KO cells ( Figure 6A ; geometric means of cell surface levels of VFG-GPI and FVG-TM were 1.85 ± 0.22 and 3.42 ± 0.99 times, respectively, those in V54KO+Vec; n = 3), suggesting its functional redundancy with TMEM87A. Recently a role for GPR107—another LU7TM family member—was shown in retrograde transport of toxins such as exotoxin A of Pseudomonas aeruginosa and ricin ( Carette et al ., 2011a ; Elling et al ., 2011 ; Tafesse et al ., 2014 ; Zhou et al ., 2014 ). Unlike TMEM87A and TMEM87B, overexpression of GPR107 or GPR108, a member of LU7TM family closely related to GPR107, did not restore the delayed transport of either VFG-GPI or FVG-TM in V54KO cells ( Figure 6B ; geometric means of cell surface levels of VFG-GPI and FVG-TM in V54KO+GPR107 were 1.21 ± 0.38 and 0.98 ± 0.11 times, respectively, those in V54KO+Vec [ n = 2], and those in V54KO+GPR108 were 1.23 ± 0.14 and 1.15 ± 0.027 times, respectively, those in V54KO+Vec [ n = 2]).…”
Section: Resultsmentioning
confidence: 99%
“…Although Gpr108 bears structural similarity to G-protein coupled receptors, to date no study has demonstrated a functional role for the protein. The related gene Gpr107 participates in the regulation of receptor-mediated endocytosis [ 10 ]. In this study Gpr108 -null mice did not show any gross phenotype whereas Gpr107 -null mice exhibited embryonic lethality.…”
Section: Discussionmentioning
confidence: 99%
“…The targeting BAC strategy used to generate Gpr108 -null mice has been previously described [ 10 , 11 ]. The targeted clones MT1 and MT2 were screened by MLPA using multiplex MLPA probes ( S1 Table ).…”
Section: Methodsmentioning
confidence: 99%
“…One practice that can protect against this is the use of two sublines of a cloned fibroblast line from a null mouse, one subline consisting of the original (null) clone of fibroblast cells transduced with an empty retroviral vector and the other consisting of the null cell clone transduced with a retroviral vector that restores the missing gene product (44). If precautions of this type are not taken, there is a possibility that the variation observed between embryonic fibroblasts isolated from different mice could reflect the properties of different populations of fibroblasts, imperiling the conclusions reached.…”
Section: Discussionmentioning
confidence: 99%